2016
DOI: 10.1002/ange.201600224
|View full text |Cite
|
Sign up to set email alerts
|

Guided Self‐Propelled Leaping of Droplets on a Micro‐Anisotropic Superhydrophobic Surface

Abstract: By introducing anisotropic micropatterns on a superhydrophobic surface, we demonstrate that water microdroplets can coalesce and leap over the surface spontaneously along a prescribed direction. This controlled behavior is attributed to anisotropic liquid–solid adhesion. An analysis relating the preferential leaping probability to the geometrical parameters of the system is presented with consistent experimental results. Surfaces with this rare quality demonstrate many unique characteristics, such as self‐powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…37,114,115 Compared with plain hydrophobic surfaces, micro/ nanostructured superhydrophobic surfaces can enable coalescence-induced droplet jumping due to the release of excess surface energy when two or more droplets merge into one. 66,[116][117][118][119][120] At small surface subcooling, typically less than one to a few K, such self-propelled droplet removal can significantly improve heat transfer efficiency in comparison with conventional dropwise condensation on plain hydrophobic surfaces (Figure 2B), which is attributed to more frequent surface refreshing. 44,78,121 However, as surface subcooling increases, the Cassie state of droplets (Figure 1H) that are easier to be removed can change to the highly pinned Wenzel state (Figure 1I), resulting in the flooding phenomenon (with a large droplet departure diameter over 4 mm) and thus greatly degrading the heat transfer efficiency of micro/nanostructured superhydrophobic surfaces.…”
Section: Context and Scalementioning
confidence: 99%
“…37,114,115 Compared with plain hydrophobic surfaces, micro/ nanostructured superhydrophobic surfaces can enable coalescence-induced droplet jumping due to the release of excess surface energy when two or more droplets merge into one. 66,[116][117][118][119][120] At small surface subcooling, typically less than one to a few K, such self-propelled droplet removal can significantly improve heat transfer efficiency in comparison with conventional dropwise condensation on plain hydrophobic surfaces (Figure 2B), which is attributed to more frequent surface refreshing. 44,78,121 However, as surface subcooling increases, the Cassie state of droplets (Figure 1H) that are easier to be removed can change to the highly pinned Wenzel state (Figure 1I), resulting in the flooding phenomenon (with a large droplet departure diameter over 4 mm) and thus greatly degrading the heat transfer efficiency of micro/nanostructured superhydrophobic surfaces.…”
Section: Context and Scalementioning
confidence: 99%
“…Droplet impact on solid surfaces has been extensively investigated owing to its significance in various fields such as hydroelectric power collection 1-4 , inkjet printing [5][6][7][8] , and anti-icing [9][10][11][12][13][14][15][16] .…”
Section: Main Text Introductionmentioning
confidence: 99%
“…Tremendous investigations have shown that SHSs with specially designed structures can retain superhydrophobicity to condensed water droplets, and coalesced droplets can be spontaneously removed from the surface via self-propelled jumping (18)(19)(20). The self-propelled jumping of condensed droplets is driven by the released surface energy during droplet coalescence after overcoming solid-liquid adhesion (21)(22)(23)(24)(25). However, these surfaces inevitably lose their water repellency at low temperatures (i.e., < −15 °C) because of freezing (9,21,26).…”
mentioning
confidence: 99%